(untitled) (Damu Journal of Sport Sciences, 2025)
The significant achievements realized in various sports activities did not arise by chance nor were they accidental; rather, they were accomplished thanks to sound scientific planning and high-level management. Management has entered the core of educational institutions and sports clubs, becoming the foundation upon which infrastructure is built. The pillars of management are the lifeblood of these institutions. This study aims to shed light on the extent to which administrative bodies in these clubs possess knowledge management concepts and their ability to employ information technology to achieve high administrative efficiency that keeps pace with modern changes in the fields of management and sports. The research problem centers on the existence of a gap in administrative work among some administrative bodies of the Iraqi Stars League clubs. It can be summarized through several questions: To what extent do members of administrative bodies possess knowledge management skills? To what extent is information technology utilized in administrative work within the clubs? What is the relationship between knowledge management and administrative efficiency? What is the relationship between information technology and administrative efficiency? Do levels of administrative efficiency differ according to varying levels of knowledge management and information technology among administrators? The study aimed to develop scales (administrative efficiency, knowledge management, and information technology) for members of the administrative bodies of the Iraqi Stars League football clubs, to identify the values of each scale and their domains, to determine the relationship and contribution ratios between knowledge management and information technology in administrative efficiency, and to derive a predictive equation for this purpose.